Utilizando um fenômeno físico para medir o diâmetro de um Fio de cabelo - Oliveira, Marina Aparecida Ferreira de (2016)
Many students finish high school without fully understanding what they are and where the physical concepts can be used. Sometimes an application enables a more meaningful learning about the concepts of this discipline. In this study, a didactic sequence is suggested in which students must solve the problem of measuring the thickness of a hair using a ruler. In this sequence, the concepts of wave and diffraction are discussed and applied to solve the problem proposed. Moreover, the study of conversion units and algebra is necessary, making this an interdisciplinary work. The kits received by state schools of Paraná can be used for the experiment, which can be applied to the students of the 3rd year of high school.